Indigenous social work field practice education: an ecosystems perspective - Engelbrecht, LK (Social Work/Maatskaplike Werk, 2001)
In this paper an attempt will be made to provide a framework for thinking about indigenous. social ·work field practice education in South Africa by means of an ecosystems perspective. This will be done by sketching the rationale and necessity for indigenous social work field practice education by clarifying the term "indigenous" and by proposing an ecological configuration of systems. South Africa currently finds itself in a period where the importance of indigenous theory and practice is greatly valued. The ecosystems perspective that this paper proposes ought therefore to make a contribution towards the establishment of indigenous social work field practice education.